Temporal trends and future projections of six major cancers among women of childbearing age in northeast Asia: analysis of data from the global burden of disease study 2021 - Liang, Jingqian; Huai, Baogeng; Yang, Zeping; Zhang, Shan; Cui, Haoliang; Zhang, Jianyi; Liu, Deshan (Frontiers in Oncology, 2025)
BackgroundCancer among women of childbearing age (WCBA) imposes major health and socioeconomic burdens, yet integrated assessments of temporal trends and future projections in Northeast Asia (NEA) are limited.MethodsUsing Global Burden of Disease 2021 estimates, we quantified incidence, mortality, and disability-adjusted life years (DALYs) for breast, cervical, uterine, ovarian, colorectal (CRC), and tracheal, bronchus, and lung (TBL) cancers among women of childbearing age (WCBA; 15–49 years) in six Northeast Asia countries from 1990–2021. We calculated age-standardized incidence, mortality and DALY rates, temporal odds ratios for the proportion of WCBA among all female cases, estimated annual percentage changes (EAPCs), and mortality-to-incidence ratios (MIRs), referencing a 46.6% threshold. Age-standardized incidence and mortality rates to 2050 were projected using Bayesian age–period–cohort models fitted with integrated nested Laplace approximation.FindingsBetween 1990 and 2021, the proportion of cancer incidence, deaths, and DALYs among WCBA relative to all females declined across all cancer types. The steepest proportional declines were for TBL incidence (ORtrend = 0.972, 95% CI: 0.969 to 0.976) and CRC deaths (ORtrend = 0.967, 95% CI: 0.965–0.969). MIRs remained below the 46.6% threshold for breast and cervical cancers, while TBL cancers persistently exceeded it (β = –0.006, 95% CI: –0.007 to –0.006). From 1990–2021, ASIRs increased for breast, cervical (EAPC = 1.58%, 95% CI: 1.49 to 1.66), cervical, and uterine cancers but decreased for ovarian cancer decreased (EAPC = –0.44%, 95% CI: –0.53 to –0.36). ASMRs declined for all cancers, most sharply for uterine cancer (EAPC = –2.38%, 95% CI: –2.68 to –2.09). ASDRs declined across cancers, most prominently for CRC (EAPC = –2.30%, 95% CI: –2.49 to –2.12). Projections to 2050 indicate continued increases in breast and uterine cancer incidence, stabilization of CRC and TBL incidence, and a sustained high cervical cancer burden in Mongolia and DPRK. Breast, uterine, and TBL cancer mortality are projected to remain stable.InterpretationAlthough mortality and DALYs among WCBA in NEA have improved, rising breast and uterine cancer incidence, persistently high lung cancer MIRs remain major concerns. Strengthened tobacco control and air-quality policies, expanded HPV vaccination and cervical screening, promotion of healthy lifestyles, and equitable access to early diagnosis and treatment are essential to reduce cross-country disparities in cancer outcomes among WCBA.